The response of weevil communities (Coleoptera: Curculionoidea) to the altitudinal zones of beech stands - J. Beránek (Journal of Forest Science, 2008)
Good knowledge of geobiocoenoses is one of the primary preconditions for biogeographical differentiation of the landscape, protected territory tending and preservation of forest ecosystems. For deepening the knowledge of the complex geobiocoenological relations the study of curculiocoenoses was conducted. It was conducted in eighteen permanent research plots based in beech stands of the 3rd, 4th and 5th altitudinal zone in the regions of South Moravia and East Bohemia. The relation of weevils to altitudinal zones was proved on the basis of some ecological index numbers and statistic methods DCA and CCA (P ≤ 0.001). It was found out that curculiocoenoses of the investigated altitudinal zones overlapped and some species decreased or increased their dominance and abundance with increasing altitude. Characteristics of the beech stand curculiocoenoses have been proposed for the 3rd, 4th and 5th altitudinal zone, which can be used as an ancillary component of the geobiocoenological or typological system. For a more complex conclusion similar research of weevils should be carried out in the beech stands of other altitudinal zones and also in other forest stands.